2020
DOI: 10.1190/geo2020-0083.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of fiber-optic strain responses to hydraulic fracturing

Abstract: We modeled cross-well strain/strain rate responses of Fiber Optic Sensing, including Distributed Strain Sensing (DSS) and low-frequency Distributed Acoustic Sensing (DAS), to hydraulic stimulation. DSS and low-frequency DAS have been used to measure strain or strain rate to characterize hydraulic fractures. However, the current application of DSS/DAS is limited to acquisition, processing, and qualitative interpretations. The lack of geomechanical models hinders the development of the technology toward quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Distributed fiber optics have also been deployed in deep boreholes, initially for monitoring of borehole casing integrity in oil and gas reservoirs (Zhou et al., 2010) but, more recently, downhole DSS has been used to monitor pumping‐induced compaction (C.‐C. Zhang et al., 2018), track the progression of hydraulic fractures in unconventional oil and gas reservoirs (Z. Zhang et al., 2020), and measure injection‐induced strains in shallow aquifers (Sun et al., 2020). While these studies convincingly demonstrated the ability of DSS to measure strains on the order of tens of microstrains ( μϵ ), borehole‐based measurements are inherently difficult to verify due to inaccessibility and the difficulty of deploying separate instruments within a single borehole.…”
Section: Introductionmentioning
confidence: 99%
“…Distributed fiber optics have also been deployed in deep boreholes, initially for monitoring of borehole casing integrity in oil and gas reservoirs (Zhou et al., 2010) but, more recently, downhole DSS has been used to monitor pumping‐induced compaction (C.‐C. Zhang et al., 2018), track the progression of hydraulic fractures in unconventional oil and gas reservoirs (Z. Zhang et al., 2020), and measure injection‐induced strains in shallow aquifers (Sun et al., 2020). While these studies convincingly demonstrated the ability of DSS to measure strains on the order of tens of microstrains ( μϵ ), borehole‐based measurements are inherently difficult to verify due to inaccessibility and the difficulty of deploying separate instruments within a single borehole.…”
Section: Introductionmentioning
confidence: 99%
“…4d,e, and f). Such evidence of nonlocalized (spatially extended) plastic deformation induced by fracture propagation (stress/hydraulic) are also observed and proven in the numerical/experimental studies (Brantut et al 2011;Huang and Chen 2021;Huang and Ghassemi 2016;Liu and Brantut 2022;Parisio et al 2021;Ramos Gurjao et al 2022;Richard et al 2021;Schmidt et al 2022;Tan et al 2021;Vinci et al 2014;Wrobel et al 2022;Zhang et al 2020).…”
Section: Geometry Of Hydraulic Fracturementioning
confidence: 60%
“…Maxwell explained polarisation by considering light as electromagnetic (vectorial) waves [36]. Quantum optics refers to more complex Schrodinger-equation-based models and determines the energy exchanged between matter and radiation [37,38].…”
Section: Characteristics and Principles Of Optical Fibresmentioning
confidence: 99%